2011
DOI: 10.1111/j.1741-2358.2011.00542.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between oral health, cognitive impairment and oral health–related quality of life

Abstract: Association between oral health, cognitive impairment and oral health-related quality of life Objective: Investigating oral health-related quality of life's (OH-QoL) relationship with cognitive state. Background: Oral health affects OH-QoL and is poor in institutionalised and cognitively impaired people. Material and Methods: This was a cross-sectional study involving 215 institutionalised elderly (82.9 mean age), who were interviewed, examined and cognitively screened using the Pfeiffer test. Results: Mean GO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 36 publications
3
28
2
4
Order By: Relevance
“…The prevalence of edentulism (33.8%) was similar to that reported for 2009 by Zuluaga et al (5), and we found a lower prevalence of edentulism and DMFT index (22.8) in the institutionalized population 65 and older than other studies in Spain (6), and also lower than those reported for catalan institutionalized elderly by 1990 in (Puigdoller A et al 1995) and for Spanish elderly by 2001 (12). These differences would respond to that those studies have analyzed oral health status for this population during 1990-2001, and their oral health status may have changed in the years which have elapsed since then.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The prevalence of edentulism (33.8%) was similar to that reported for 2009 by Zuluaga et al (5), and we found a lower prevalence of edentulism and DMFT index (22.8) in the institutionalized population 65 and older than other studies in Spain (6), and also lower than those reported for catalan institutionalized elderly by 1990 in (Puigdoller A et al 1995) and for Spanish elderly by 2001 (12). These differences would respond to that those studies have analyzed oral health status for this population during 1990-2001, and their oral health status may have changed in the years which have elapsed since then.…”
Section: Discussionsupporting
confidence: 90%
“…Collectively, it can be cost-effective for information on oral health in adult and elderly populations. Purposely, previous studies using GOHAI in Spanish institutionalized elderly populations have reported a high prevalence of poor OHRQoL (5,6). …”
Section: Introductionmentioning
confidence: 99%
“…Zuluaga and colleagues reported that persons with mild or moderate cognitive impairment had better oral health-related QoL than persons with normal cognitive function. 17 One likely explanation for this difference is that the study by Zuluaga used a 10-item cognitive screening measure to determine the diagnosis of mild and moderate cognitive impairment. Such brief cognitive measures are neither valid nor reliable for the diagnosis of complex disorders such as mild cognitive impairment or dementia.…”
Section: Discussionmentioning
confidence: 99%
“…16 On the other hand, another study conducted in Spain found participants with mild cognitive impairment had significantly better self -reported oral health measured by the Geriatric Oral Health Assessment Index (GOHAI) than participants with normal cognition. 17 Both studies were limited by the use of brief mental status instruments to determine cognitive status. Such measures do not provide valid diagnoses of mild cognitive impairment or dementia.…”
Section: Introductionmentioning
confidence: 99%
“…La percepción de la salud oral es frecuentemente negativa en ésta población ya que tienden a aceptar las enfermedades bucales como consecuencia del envejecimiento. Sólo el 23,4% percibió como buena su calidad de vida relacionada con la salud oral, valor inferior a lo observado por otros autores (27,28,29,30).…”
Section: Discussionunclassified